ANALISIS STANDAR PENILAIAN PENDIDIKAN DASAR DI INDONESIA - Syalsa Riski Maulina; Azzahra; Elsa Febriani; Rizki Ananda (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Evaluation or assessment in education is one of the components of the curriculum so that evaluation or assessment is urgent and cannot be separated from other curriculum components. Evaluation or assessment is important because it is made the National Education Standard in Law No. 20 of 2003. The purpose of this research is to analyze the assessment standards in Indonesia in Permedikbud Number 23 of 2016, Permendikbud Number 21 of 2022, and PP Number 19 of 2005. This research is a literature study with the method used, namely Systematic Review (SR) or generally called Systematic Literature Review (SLR) is a systematic technique for collecting, critically examining, integrating and collecting the results of various research studies on research questions or topics to be explored. This research found Permendikbud Number 23 of 2016, Educational Assessment Standards include criteria regarding the scope, objectives, benefits, principles, mechanisms, procedures and assessment instruments.  Permendikbudristek Number 21 of 2022 found that Education Assessment Standards include minimum criteria regarding assessment mechanisms. Government Regulation No. 19 of 2005 Educational assessment at the primary and secondary education levels consists of: a) assessment of learning outcomes by educators; b) assessment of learning outcomes by education units; and c) assessment of learning outcomes by the government. Keywords: analysis, assessment standards, education